FAMILY RICHARDIIDAE - Wendt, Lisiane Dilli; Ale-Rocha, Rosaly (Zootaxa, 2016)
Richardiidae are a family of “acalyptrate” Diptera represented by ca. 180 species distributed in the New World, mostly in the Neotropical region. The species that occur in Colombia have received little attention from taxonomists, and the great majority of them are known only from their type localities. Currently, 14 genera and 23 species are known to occur in the country.